The reading of legal cases by law undergraduates: some problems and suggestions - Ariffin, Adlina (Elsevier, 2014)
The ability to read legal cases is one of the most essential skills for law students aiming for success in their discipline. It is particularly fundamental since case law is one of the main sources of law. Christensen (2006) in her research entitled “Legal Reading and Success in Law School: An Empirical Study” shows that students who are able to read judicial opinions effectively and efficiently are more successful in their studies. However, the most common assumption is that students already possess this skill when they enrol in a law school. This attitudinal fallacy is referred to as “skills deployment assumption” (Stratman, 1990). Thus, this paper describes a research study which investigates the quintessential elements in the reading of legal cases among law students in a Malaysian public university. Its specific aims were to develop some understanding about the reading of this rhetorical genre and simultaneously to uncover the problems related to the learning process. In this research, a case study design was adopted and data was obtained through interview sessions with twelve law students. The major findings of this research show that despite the training given to the students, they still face a lot of problems in acquiring this crucial skill. These challenges emanated from three main aspects, i.e. language, time management and the nature of legal cases.